Social anxiety disorder and its impact in undergraduate students at Jazan University, Saudi Arabia - Ramzi M. Hakami; Mohamed S. Mahfouz; Abdulrahman M. Adawi; Adeebah J. Mahha; Alaa J. Athathi; Hadi H. Daghreeri; Hatim H. Najmi; Nuha A. Arishi (Mental Illness)
Although social anxiety disorder (SAD) is a common mental disorder, it is often under diagnosed and under treated. The aim of this study is to assess the prevalence, severity, disability, and quality of life towards SAD among students of Jazan University, Saudi Arabia. A cross-sectional study was conducted among a stratified sample of 500 undergraduate students to identify the prevalence of SAD, its correlates, related disability, and its impact on the quality life. All participants completed the Social Phobia Inventory, Leibowitz Social Anxiety Scale, Sheehan Disability Scale, and the WHO Quality of Life – BREF questionnaire. Of 476 students, 25.8% were screened positive for SAD. About 47.2% of the students had mild symptoms, 42.3% had moderate to marked symptoms, and 10.5% had severe to very severe symptoms of SAD. Students who resulted positive for SAD reported significant disabilities in work, social, and family areas, and this has adversely affected their quality of life as compared to those who screened negative for SAD. Students reported several clinical manifestations that affected their functioning and social life. Acting, performing or giving a talk in front of an audience was the most commonly feared situation. Blushing in front of people was the most commonly avoided situation. Since the present study showed a marked prevalence of SAD among students, increased disability, and impaired quality of life, rigorous efforts are needed for early recognition and treatment of SAD.